"Rendering the Majority Unable": Comparative Politics, Social Inequality, and the United States' Institutional Structure of Political Suboptimality. (December 2016) - Alemán, David Mena
The Founding Fathers conceived formal counter-majoritarian restrictions aimed specifically to "render the majority unable": to prevent the majority from trampling on minorities in the U.S. democratic system. This article contends that several such formal restrictions actually fail to protect contemporary minorities as the founders imagined they would. Indeed, counter-majority restrictions embedded in the Electoral College, the Senate, and the judicial review may actually prohibit such protection. Using a comparative politics approach, this article builds on theoretical arguments and data that evaluate democratic functionality and fairness based on level of social equality provisions as well as optimality of voter participation. I find that certain counter-majoritarian procedures are empirically linked to higher inequality levels across twenty-one advanced democracies. This political suboptimality is reflected in a significant correlation between higher Gini coefficients and majoritarian systems (with the United States in first place) in the sample and also between lower scores and consensus democracies. I argue that comparative analysis shows that some criticisms hitherto only leveled at the United States are present in an entire family of systems—the majoritarian ones—which begs significant critical questioning of the impact of institutional design on the effectiveness of social policies and inclusive democratic procedures.